Downsizing - Gerard A. Pfann (Institute for the Study of Labor (IZA), 2001)
Optimal layoff rules in closed form are derived for all workers in a firm that downsizes under uncertainty and faces heterogeneous firing costs. The theoretical model predicts that the firm displaces workers with low firing costs, low expected future productivity growth, and low layoff option values. The empirical analysis based on personnel records from a Dutch aircraft building company that went bankrupt in 1996 shows that workers with high uncertainty associated with higher than average expected productivity growth are most likely to be retained.
Keywords: J33; J63; 330; Layoff rules; firing costs; uncertainty; heterogeneity; Personalabbau; Kündigung; Kosten; Arbeitsproduktivität; Entscheidung bei Unsicherheit; Luftfahrtindustrie; Theorie; Niederlande; Koninklijke Nederlandse Vliegtuigenfabriek; Fokker <Amsterdam>